Asosiasi Moluska (Gastropoda dan Bivalvia) Pada Ekosistem Magrove di Muara Sungai Kumbe - Martha Welistin Katukdoan; Nova Suryawati Monika; Sunarni Sunarni (AGRICOLA, 2018)
This study aims to determine the types of gastropods and bivalves associated with mangrovevegetation. Data analysis convering density, diversity, dominance, uniformity of Gastropods andBivalves with mangrove density at Kumbe estuary of Merauke Regency, which was held for twomonths from August to September 2016. The method used was the line transect method with a plotmeasuring 10x10 meters and for molluscas using 1x1 meter plot. The results showed that themolluscas were found of exhibit association of mangrove vegetation in both stations consisting of 9types of Gastropods and 2 types of Bivalves. Species diversity (H') is highest in Station II (river moutharea) and moderate species diversity in Station I (residential area). Uniformity (E’) shows a stablevalue at both stations. Dominance (D) is included in the low value or no type of Gastropoda andBivalvia that dominates at both stations. There are 9 types of mangroves with the highest density ofmangroves in Station I and the lowest in Station II